Gender differences in prosocial behavior: Organizational citizenship behavior - Dávila de León, María Celeste; Finkelstein, Marcia A.; Castien, Juan Ignacio (Anales de Psicología / Annals of Psychology, 2011)
Organizational citizenship behaviors (OCB) are workplace activities that exceed an employee’s formal job requirements and contribute to the effective functioning of the organization. The behaviors may be directed toward co-workers or the organization itself. The purpose of this study is analyzes the gender differences in OCB following functional analysis and role identity theory. A total of 974 employees completed surveys measuring OCB motives, strength of organizational citizen role identity, and amount of OCB. The results showed that females do OCB aimed at individuals with more frequency, give more importance to prosocial values motive (desire to help others and to be accepted by them) and have a greater role identity like organizational citizen that help to workmates than males. When we analyze the predictive role of motives and role identity, we didn’t find relevant differences between females and males. The findings are discussed with regard to diverse theories.